2020
DOI: 10.34067/kid.0000072020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Response and Pattern of B cell Suppression with Single Low Dose Rituximab in Nephrology

Abstract: Background There is no consensus regarding dose and frequency of rituximab in Nephrology with extrapolation of dose used in treating lymphoproliferative disorders. There are no guidelines on targeting initial and subsequent doses based on CD19 + B cells. Methods 100 mg rituximab was given initially in 42 adults with steroid dependent (SDNS) and frequently relapsing nephrotic syndrome (FRNS), idiopathic membranous nephropathy (MN) and high immunologic risk kidney transplantation. Absolute and percentage CD19 B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…One male patient received additional dose of rituximab based on CD 19 B cell count as a part of his treatment strategy. The need to repeat rituximab injection in our cases was based on the criteria of CD 19 B cell count being greater than five cells/µL, which was similar to the algorithm proposed by Jacob George et al (14). Higher PLA2R titre with more chronicity on renal biopsy can be considered as a possible explanation for poor response to rituximab as seen in patient 4 (15).…”
Section: Discussionmentioning
confidence: 60%
“…One male patient received additional dose of rituximab based on CD 19 B cell count as a part of his treatment strategy. The need to repeat rituximab injection in our cases was based on the criteria of CD 19 B cell count being greater than five cells/µL, which was similar to the algorithm proposed by Jacob George et al (14). Higher PLA2R titre with more chronicity on renal biopsy can be considered as a possible explanation for poor response to rituximab as seen in patient 4 (15).…”
Section: Discussionmentioning
confidence: 60%
“…It may be possible to combine induction agents acting at different sites. ATG targets T cells and as Rituximab targets B cells, there may be a role in combining both [9,21,22]. Though a combination of ATG and IL2Ra has not been recommended [12], there are reports of combining ATG or IL2RA with rituximab in selected patients [9,21,22].…”
Section: Can Induction Agents Be Combined?mentioning
confidence: 99%
“…A single dose of 375 mg/m2 was effective in reducing the incidence of AMR in immunologically high-risk patients [31]. It has been shown that doses as low as 100 mg in renal transplantation while on other immunosupressants can produce prolonged CD19B cell suppression for even a year justifying avoiding the weekly doses used in lymphoproliferative disorders [22]. The cost of 100 mg Rituximab is INR3000 (US$40) making it one of the potentially cheapest induction agent.…”
Section: Can a Reduced Dose And Frequency Of Induction Immunosuppress...mentioning
confidence: 99%
See 2 more Smart Citations